Synthesis of triphenylene-fused phosphole oxides via C–H functionalizations - Rahman, Md. Shafiqur; Yoshikai, Naohiko (Beilstein Journal of Organic Chemistry, 2020)
The synthesis of triphenylene-fused phosphole oxides has been achieved through two distinct C–H functionalization reactions as key steps. The phosphole ring was constructed by a three-component coupling of 3-(methoxymethoxy)phenylzinc chloride, an alkyne, and dichlorophenylphosphine, involving the regioselective C–H activation of the C2 position of the arylzinc intermediate via 1,4-cobalt migration. The resulting 7-hydroxybenzo[b]phosphole derivative was used for further π-extension through Suzuki–Miyaura couplings and a Scholl reaction, the latter closing the triphenylene ring. The absorption and emission spectra of the thus-synthesized compounds illustrated their nature as hybrids of triphenylene and benzo[b]phosphole.
Keywords: C–H functionalization; fluorescence; phosphole; polycyclic aromatic hydrocarbons; triphenylene